Mycoplasma in human umbilical cord blood : its isolation, identification and characterization with reference to congenital mycoplasma infections - Steytler, Johann Georg (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.D.) -- University of Stellenbosch, 1969.